Simulating ecosystem carbon dioxide fluxes and their associated influencing factors for a restored peatland - H. He; I. B. Strachan; N. T. Roulet (Biogeosciences)
Restoration of drained and extracted peatlands can potentially return them to carbon dioxide (CO2) sinks, thus acting as significant climate change mitigation. However, whether the restored sites will remain sinks or switch to sources with a changing climate is unknown. Therefore, we adapted the CoupModel to simulate ecosystem CO2 fluxes and the associated influencing factors of a restored bog. The study site was a peatland in eastern Canada that was extracted for 8 years and left for 20 years before restoration. The model outputs were first evaluated against 3 years (representing 14–16 years post-restoration) of eddy covariance measurements of net ecosystem exchange (NEE), surface energy fluxes, soil temperature profiles, and water table depth data. A sensitivity analysis was conducted to evaluate the response of the simulated CO2 fluxes to the thickness of the newly grown mosses. The validated model was then used to assess the sensitivity to changes in climate forcing. The CoupModel reproduced the measured surface energy fluxes and showed high agreement with the observed soil temperature, water table depth, and NEE data. The simulated NEE varied slightly when changing the thickness of newly grown mosses and acrotelm from 0.2 to 0.4 m but showed significantly less uptake for a 1 m thickness. The simulated NEE was -95±19<mspace width="0.125em" linebreak="nobreak"/>g<mspace linebreak="nobreak" width="0.125em"/>C<mspace width="0.125em" linebreak="nobreak"/>m-2<mspace width="0.125em" linebreak="nobreak"/>yr-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="104pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="87eede722685d851a9097df4f18c8042"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-22-1355-2025-ie00001.svg" width="104pt" height="15pt" src="bg-22-1355-2025-ie00001.png"/></svg:svg> over the 3 evaluation years and -101±64<mspace linebreak="nobreak" width="0.125em"/>g<mspace linebreak="nobreak" width="0.125em"/>C<mspace width="0.125em" linebreak="nobreak"/>m-2<mspace linebreak="nobreak" width="0.125em"/>yr-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="110pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="c026dd05a905dd2d7a95dfa3d48e09f0"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-22-1355-2025-ie00002.svg" width="110pt" height="15pt" src="bg-22-1355-2025-ie00002.png"/></svg:svg>, ranging from −219 to +54<mspace width="0.125em" linebreak="nobreak"/>g<mspace width="0.125em" linebreak="nobreak"/>C<mspace width="0.125em" linebreak="nobreak"/>m-2<mspace linebreak="nobreak" width="0.125em"/>yr-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="80pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="5e8fd221120e057e7dcae48f5531e4b2"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-22-1355-2025-ie00003.svg" width="80pt" height="15pt" src="bg-22-1355-2025-ie00003.png"/></svg:svg>, with extended 28-year climate data. After 14 years of restoration, the peatland has a mean CO2 uptake rate similar to pristine sites but with a much larger interannual variability, and in dry years, the restored peatland can switch back to a temporary CO2 source. The model predicts a moderate reduction in CO2 uptake but still a reasonable sink under future climate change conditions if the peatland is ecologically and hydrologically restored. The ability of the CoupModel to simulate the CO2 dynamics and its thermo-hydro-drivers for restored peatlands has important implications for emission accounting and climate-smart management of drained peatlands.